Судові витрати як складова принципу доступу до правосуддя в цивільному судочинстві європейських країн - Гайдар, М. В.; Haidar, M. V.; Шуміло, О. М.; Shumilo, O. M.; Марина Гайдар (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 2 (109). - С. 59-65, 2025)
У статті досліджено досвід іноземних держав у забезпеченні доступу до правосуддя через регулювання судових витрат. Проаналізовано підходи до оптимізації фінансових бар’єрів, зокрема впровадження цифровізації, механізмів державної правової допомоги, групових позовів і медіації. Розглянуто вплив судового збору на доступність судочинства та заходи з його врегулювання. Зроблено висновки про необхідність комплексного підходу до регулювання судових витрат для забезпечення справедливого й доступного правосуддя.

Access to justice is a fundamental principle in legal systems worldwide, ensuring that individuals can effectively exercise their rights and seek redress through the judiciary. This paper examines the experience of foreign states in facilitating access to justice through judicial expenses, particularly in the context of digitalization, group lawsuits, court fees, and mediation. The study is based on a comparative legal analysis of different judicial systems and their approaches to reducing financial barriers for litigants. The research explores how various countries have implemented measures to enhance judicial accessibility, including fee waivers, state-funded legal aid programs, and alternative dispute resolution mechanisms. Particular attention is given to the role of digitalization in streamlining court procedures, reducing costs, and improving efficiency in case management. The paper highlights the significance of online dispute resolution platforms and electronic filing systems in promoting greater access to justice. Additionally, the article delves into the impact of court fees on litigants and assesses the effectiveness of policies aimed at balancing the financial sustainability of judicial institutions with the need for equitable access. The study also discusses the role of class actions in providing an avenue for collective redress, particularly in cases where individual litigation would be prohibitively expensive. The findings underscore the necessity of a balanced approach to judicial expenses, ensuring that cost structures do not deter individuals from pursuing legitimate claims. Recommendations are provided for policymakers to adopt best practices from international experiences, fostering a more accessible, efficient, and fair legal system.
Experience of European countries in ensuring access to justice through legal costs
Keywords: цифровізація; судові витрати; доступність правосуддя; групові позови; судовий збір; медіація; digitalization; court costs; access to justice; class action lawsuits; court fee; mediation